Carcinoma in situ of the testis: aneuploid cells in semen. Issue 6639 (25th June 1988) - Giwercman, Aleksander; Clausen, Ole Petter F; Skakkebæk, Niels E
Abstract : The content of cellular DNA in ejaculates from eight patients with carcinoma in situ of the testis and 26 controls without evidence of testicular neoplasia was studied by flow cytometry. An aneuploid cell population with a ploidy value similar to that found for carcinoma in situ cells was detected in seminal fluid from four of the eight men with carcinoma in situ but in none of the controls. One year after orchidectomy or local irradiation in these four men no aneuploid cells were found in the semen. These findings show that a detectable proportion of malignant germ cells may be released into the seminal fluid of patients with carcinoma in situ of the testis. Analysis of seminal fluid may therefore aid in screening for early neoplasia of the testis.